Lean Implementation and Organisational Agility: The Mediating Role of Continuous Improvement Culture in Nigerian Manufacturing Firms (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study investigates the relationship between lean implementation (LI) and organisational agility (OA) in Nigerian manufacturing firms, with a focus on the mediating role of continuous improvement culture (CIC). Drawing upon the dynamic capabilities and organization culture perspectives, we argue that lean practices provide process discipline and visibility, while a culture of continuous improvement transforms these practices into adaptive organisational capabilities. Data were collected through a cross-sectional survey of 54 listed manufacturing firms. Partial Least Squares Structural Equation Modelling (PLS-SEM) was employed to test the proposed model. The findings indicate that LI has a significant positive effect on OA, and CIC mediates this relationship. The study concludes that lean practices enhance agility most effectively when accompanied by strong learning and improvement-oriented cultures. Implications for managers and policy makers are discussed.